Local versus global price cap: A comparison of foreclosure incentives - Gert Brunekreeft (Albert-Ludwigs-Universität Freiburg, Institut für Verkehrswissenschaft und Regionalpolitik, 1997)
This paper compares two regulatory devices for handling (access to) bottlenecks in deregulated network industries: (1) a local price cap and (2) a global price cap, the latter of which applies the efficient component pricing rule. The local price cap restricts profit regulation to the bottleneck, whereas a complementary set of measures intends to curb the resulting incentives for foreclosure of the competitive markets. The global price cap extends regulation to the entire firm, which should take away the foreclosure incentives. This major advantage of the global price cap is contrasted to possible disadvantages, which centre around renewed foreclosure incentives.
Keywords: L43; L51; L9; 330; Netzzugang; Anreizregulierung; Markteintritt; Theorie